Valorization of Tropical Fruit Peels into Sustainable Food Crackers: Development, Utilization, and Consumer Acceptability - Pelaje, Roel Marlon; Velasco, Joram Owen; Elizon, Jushua; Henson, Orland Nathanniel; Abay, Irish; Comendador, Hersheys; Dela Cruz, Prince Emmanuel; Divina, Alfel Jay; Junsay, Maysie; Pallada, Cris Anne Kaye; Villanada, Jann Calvin; Aquino, Rommel (Journal of Interdisciplinary Perspectives, 2025)
This study explores the valorization of tropical fruit peels—specifically dragon fruit, durian, guyabano, jackfruit, marang, and pineapple—into sustainable food crackers through experimental development, laboratory testing, and sensory evaluation. The formulated crackers demonstrated positive phytochemical profiles, including flavonoids, phenols, and proteins, confirming their potential as functional food products. Microbiological analyses indicated compliance with safety standards, while proximate composition revealed desirable nutritional properties, including high carbohydrate content and moderate protein and fiber content. Sensory evaluation among faculty, students, and community respondents yielded an overall mean rating of 4.48 (“Like Extremely”), with texture and appearance rated highest. ANOVA results (p = 0.037) indicated significant differences among respondent groups, highlighting varying sensory preferences. The findings affirm that tropical fruit peel crackers are nutritionally beneficial, safe, and consumer-acceptable, offering a sustainable solution for waste reduction, food innovation, and environmental protection aligned with circular economy principles and the United Nations Sustainable Development Goals.